The Influence of Students Personality on Their Peer Review Ability - Darwis, Nirwana; Iwanawulansari, Iwanawulansari; Amal, Nur Ikhsan (DIDAKTIKA, 2023)
This study was aimed at investigating whether there is a significant influence between extrovert and introvert students in Verbal Peer Review ability. This study belongs to ex post facto design with a quantitative approach. For the data collection, there were questionnaires and speaking tests as the instruments. The questionnaire was adapted from the Eysenck Personality Questionnaire (EPQ) which categorized the students into introvert and extrovert. The population of this study was the students of XI MIPA 2 at SMAN 1 Bone with a total of 34 students, with a sample of 20 students who had been assigned purposive sampling technique of the population. The result found that there were 13 extroverts, 5 ambivalent, and 16 introverts. The result of the peer review test is the extrovert students' achievement was 16,6 and the introvert students' achievement was 8,6 as the average for their speaking ability. Both the questionnaire and peer review test results were then analyzed by using Pearson Correlation. It found out the correlation was significant at the 0.01 level. Meanwhile, the basic determination of Pearson Correlation was if the Sig. < 0,05 so the variables were correlated. Based on the result of the study, the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. In conclusion, there is a significant influence of students' personalities on the peer review ability of XI MIPA 2 at SMAN 1 Bone.